Analysis of Salmonella lineage-specific traits upon cell sorting - Fernández-Fernández, Rocío; López-Igual, Rocío; Casadesús, Josep; Sánchez-Romero, María Antonia (Frontiers in Cellular and Infection Microbiology, 2023)
Cell individuality in bacteria is receiving increasing interest in the scientific community because of its effect on gene expression, survival under selective conditions and stresses and pathogen-host interactions. The advent of fluorescent protein technology and advances in single-cell analysis has unveiled scores of phenotypic cell variant in bacterial populations. Last few years, numerous cell sorting approaches have been employed for resolving the properties of bacterial subpopulations. This review provides an overview of applications of cell sorting to analyze Salmonella lineage-specific traits, including bacterial evolution studies, gene expression analysis, response to diverse cellular stresses and characterization of interesting cells with different purposes.